Notational Analysis of Sport - Hughes, M.; Franks, I. M.; Bartlett, R.; Cooper, S. M.; Evans, S.; Hodges, N. J.; Liebermann, D. G.; McGarry, T.; More, K.; Nevill, A.; Perl, J.; Wells, J. (Routledge, 2004)
Notational analysis is used by coaches and sport scientists to gather objective data on the performance of athletes. Tactics, technique, individual athlete movement and work-rate can all be analysed, enabling scientists, coaches and athletes to learn more about performance and gain a competitive advantage. Systems for notational analysis are becoming increasingly sophisticated, reflecting the demands of scientists in technology. This 2nd edition contains updated information about all the new technology and a review of the latest notational analysis research.